Comprehensive Review of Pharmacogenomics and The Expanding Scope of Pharmacy Practice in Precision Medicine - almoyed, Gassim hassan Mohammed; Alsharif, Hamzah Khaled M; Alshareef, Ahamed Mohammed; Alofair, Saeed Ali Hussain; Al yaseen, Mansour Mohammed; Yaseen, Hamad Mahdi Faris; Aldosari, Ahmad Samran Ali; Al shareef, Ali Mohammed Hussein; Alaglah, Moslah Hussain Moslah; Alhashel, Ibrahim Saleh Hamad (Journal of Ecohumanism, 2024)
This review aims to examine the relevance of understanding pharmacogenomics to develop precision medicine and the broadening role of pharmacy in this field. Pharmacogenomics, the study of genetic factors affecting drug action, has emerged as an essential component in clinical practice, thus providing individualized therapy. The paper aims to provide a background of pharmacogenomics, identify its current use in healthcare, and discuss the possibility of pharmacies incorporating and enhancing drug therapy. It considers such issues as pharmacogenomics/pharmacy bottlenecks, potential benefits, and consequences for patients, and the costs and responsibilities of the pharmacists and pharmaceutical organizations for pharmacogenomic-based treatments. The review’s author provides suggestions for merging pharmacogenomics even more into clinical practice and pharmacy education.